Mathematical analysis for a system of nonlinear ordinary differential equations related to ethanol production - Ahmad Izul Fakhruddin, Azimi; Norazaliza, Mohd Jamil (Akademi Sains Malaysia, 2019)
The fermentation process is a crucial stage in transforming substrate to ethanol. Ethanol is obtained by fermenting the substrate using microbial such as yeasts or bacteria. This process can be explained in a system of nonlinear Ordinary Differential Equations (ODEs) mathematical model. The broad understanding of the model can improve the prediction of ethanol production yield. In this paper, the stability analysis is done to investigate the stability of the proposed model and followed by the investigation of its parameter behaviour towards the model.